"SOCIAL FACTORS AFFECTING THE CHANGE IN THE CHARACTER OF YOUTH IN THE CONDITIONS OF GLOBALISATION AND THEIR PSYCHOLOGICAL SOLUTIONS" (Universal International Scientific Journal, 2026)
This scientific article scientifically analyzes the main social factors that affect the formation and change of youth character. In the course of the research, the influence of the family environment, the education system, peer group, the media, and socio-economic conditions in society on the psychological development of youth was studied. The psychological mechanisms of changes in the character of youth and psychological solutions aimed at ensuring their positive formation were also highlighted. The results of the study show that a healthy social environment, an effective educational process, and psychological support are important in developing positive character qualities in young people. The article also provides practical recommendations for preventing negative changes in the character of youth and strengthening their psychological stability.
Keywords: : youth psychology, character formation, social factors, socialization process, family environment, education system, peer group, media, psychological development, psychological support, personal development, social environment